Implementation Plan in Response to Board-Endorsed Recommendations Arising from the Independent Evaluation Office Report on The IMF and Aid to Sub-Saharan Africa. (Policy Papers; Policy Paper ;, 2007)
This paper sets out an implementation plan that responds to the IEO report on the Fund and Aid to Sub-Saharan Africa (the IEO Report). It sets out the recommendations made in the IEO Report and the view of the Executive Board on them (Section II), and outlines the various work streams that are being undertaken to respond substantively to the recommendations endorsed by the Board (Section III). The paper also estimates the cost of the first stage of the Fund's response to the IEO Report, while costings for proposals in the implementation phase will be provided in the context of forthcoming Board papers. Finally, the paper solicits Directors' feedback.